ANALISIS PENGARUH ANALISIS KONSTRUKSI BERTAHAP (CONSTRUCTION SEQUENCE ANALYSIS) TERHADAP EKSENTRISITAS KOLOM BETON BERTULANG - Ardyansah, Rofika Ratna; Suryanita, Reni; Djauhari, Zulfikar (Universitas Pendidikan Nasional, 2018)
In reality, a building structure was built floor by floor or gradually, this is going to affectforces in preliminary design (using Direct Loading Method). The most extreme effect in the form ofeccentricities in the column structure, there this research is giving depiction on how far eccentricitiesdeviation dan what factor affects column structure eccentricities as the consequence of gradualbuilding.This research utilizes Sequential Loading Method, that is weight loading method by trying toimitate loading while construction execution occured with loading weight on gradual and sequentialstructre model.Eccentricities on column structure will extremely decrease if axial weight was added(column with one floor above). This research show eccentricites decrease until 26.39% or decrease asmuch as 73.61% from Full Model analysis. Bekisting dismantling before structure column and floorweight above done correctly is the main factor for a extensive eccentricites on column structure tohappen. So, bekisting dismantling should be planned very well by calculating its structure behavior.